Ligand-dependent transformation by the receptor for human granulocyte/macrophage colony-stimulating factor and tyrosine phosphorylation of the receptor beta subunit. - Areces, L B (1993)
The receptor for human granulocyte/macrophage colony-stimulating factor (hGMR) is composed of two subunits, alpha and beta, which are both required for high-affinity binding of the ligand. To examine the transforming potential of hGMR, we have transfected cDNAs encoding the receptor alpha and beta subunits into NIH 3T3 cells, which normally do not express GMRs. Introduction of the receptor subunits into these cells resulted in focal transformation, which was dependent on the presence of human granulocyte/macrophage colony-stimulating factor (hGM-CSF) in the culture medium. No transformation was observed when hGM-CSF was replaced with other growth factors such as human epidermal growth factor or human interleukin 3 or when cells were transfected with the alpha or beta subunit alone. Individual conditional transformants isolated after transfection expressed functional hGMRs, were susceptible to transformation by picomolar levels of the ligand, and were capable of anchorage-independent growth in soft agar in the presence but not in the absence of hGM-CSF. Biochemical analysis showed that treatment of these cells with hGM-CSF caused a rapid phosphorylation of the beta subunit and other cellular proteins on tyrosine residues, recapitulating some of the events that take place during GM-CSF signaling in myeloid cells. We conclude that coexpression of the alpha and beta subunits of hGMR in established murine fibroblasts is sufficient to reconstitute a functional receptor, which is capable of causing ligand-dependent transformation. The oncogenic potential of hGMR lends support to the hypothesis that its deregulated or abnormal expression may play a role in leukemogenesis.